2012
DOI: 10.1038/cdd.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar protein GLTSCR2 stabilizes p53 in response to ribosomal stresses

Abstract: p53 is a key regulator of cell growth and death by controlling cell cycle progression and apoptosis under conditions of stress such as DNA damage or oncogenic stimulation. As these processes are critical for cell function and inhibition of tumor development, p53 regulatory pathways are strictly monitored in cells. Recently, it was recognized that nucleolar proteins, including nucleophosmin/B23, ribosomal protein L11, and alternate reading frame (ARF), form the nucleolus-ARF-murine double minute 2 (MDM2) axis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 42 publications
0
59
0
2
Order By: Relevance
“…The induction of Myc in conditions of mitochondrial stress may serve an adaptive function of stimulating glucose uptake and glycolysis to compensate for the impairment of oxidative phosphorylation, while also attempting to restore mitochondrial activity. Previous studies have suggested that GLTSCR2 is induced by genotoxic stressors, such as ionizing radiation and UV radiation, and low-dose actinomycin D, which is thought to cause ribosomal stress by inhibiting rRNA synthesis (28,29). It is possible that some of these agents may also impinge upon mitochondrial function and activate pathways leading to the induction of GLTSCR2.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of Myc in conditions of mitochondrial stress may serve an adaptive function of stimulating glucose uptake and glycolysis to compensate for the impairment of oxidative phosphorylation, while also attempting to restore mitochondrial activity. Previous studies have suggested that GLTSCR2 is induced by genotoxic stressors, such as ionizing radiation and UV radiation, and low-dose actinomycin D, which is thought to cause ribosomal stress by inhibiting rRNA synthesis (28,29). It is possible that some of these agents may also impinge upon mitochondrial function and activate pathways leading to the induction of GLTSCR2.…”
Section: Discussionmentioning
confidence: 99%
“…37 This results in significant changes in its functional properties as a transcription factor. [38][39][40][41][42][43] As a consequence of the p53 isoforms function as a transcription factor and its involvement in DNA damage, it is evident that the status of p53 plays a crucial role in cancer progression [44][45][46][47][48][49][50][51][52] as well in different physiological 2 and anticancer responses. 42 In fact, p53 is frequently mutated in cancer, resulting in novel "gain-of-function"effects.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the transcription level of these genes was found to increase or decrease with increasing fish HSI. This could be linked, at least in part, to the fact that these genes are not only involved in protein translation but also in cell cycle by regulating the accumulation of the p53 protein in cell (Horn and Vousden 2008;Lee et al 2012). The p53 protein is involved in cell cycle arrest and apoptosis.…”
Section: Hepato-somatic Indexmentioning
confidence: 99%